Prospective Investigation of the Interaction Between Social Problems and Neuropsychological Characteristics on the Development of Suicide Ideation. Issue 2 (4th December 2019) - McManimen, Stephanie; Wong, Maria M.
Abstract : Objective: Negative social interactions are known to contribute to the development of suicide ideation. However, it is unclear how this risk factor interacts with other predisposing risk factors. The purpose of this study was to determine how social and neuropsychological factors interact as a prospective predictor of the emergence of suicide ideation in adolescents. Method: Data were collected from adolescents ( M age = 13.12, SD = 1.48) over 3 years as part of a larger study. Participants completed the MINI‐Kid and Youth Self‐Report, which were used to assess for suicidality. Negative social interactions were operationalized as the Social Problems scale of the YSR. Additionally, adolescents completed a neuropsychological battery at each wave of data collection. Results: Logistic moderation analyses demonstrated a significant interaction between task switching and endorsement of negative social interactions in the prediction of suicide ideation one year later, Wald χ 2 (1) = 4.94, OR = 0.90, p < .05. Distractibility was a significant predictor, Wald χ 2 (1) = 5.52, OR = 3.45, p < .05, but it did not demonstrate an interaction effect. Perseveration failed to reach statistical significance independently and in the interaction. Conclusions: The results indicate that certain neuropsychological characteristics can aid in predicting which adolescents will develop suicide ideation in the presence of negative social interactions, which may have significant clinical implications.